Assessment of the toxicity and the fertilizing power from application of gamma irradiated anaerobic sludge as fertilizer: Effect on Vicia faba growth. (September 2018) - Limam, Rim Driss; Limam, Intissar; Clérandeau, Christelle; Khouatmia, Mohamed; Djebali, Wahbi; Cachot, Jérôme; Chouari, Rakia
Abstract: With increasing sludge produced every day by wastewater treatment plants, new methodologies have been developed to reduce sludge or to valorize them at lower cost and energy. Among these methodologies, agricultural manuring is of great interest as sludge could complement or replace chemical fertilizers. However, sludge pretreatment was necessary prior to its use in order to eliminate the degradable organic contaminants, heavy metals and diverse pathogenic microorganisms. In this study we performed γ-irradiation of anaerobic sludge coming from wastewater treatment plants at different doses (0.5, 1.5, 2.5, 3.5 and 4.5 kGy), followed by anaerobic digestion. We then used them in addition to soil for Vicia faba cultures. Heavy metal concentrations, toxicological evaluations, and the number of cultivable pathogenic bacteria were also investigated in irradiated and non-irradiated sludge samples to determine the effect of γ-irradiation on toxicity and pathogens present in the sludge. Results show that 4.5 kGy is the optimal dose, and γ-irradiation pretreatment of anaerobic sludge added to soil (2 mL/30 g) has significantly improved Vicia faba growth. Furthermore, by eliminating pathogens and by degrading chemical pollutants, γ-irradiation of anaerobic sludge provides promising insights for re-using sludge as a safe fertilizer. Highlights: The effect of the γ-irradiations on the pathogenic microorganism. Evaluation of chemical toxicity of irradiated anaerobic sludge. The irradiation of sludge allows heavy metals to be more easily released. The gamma irradiated anaerobic sludge could be used as safe fertilizers.